2017
DOI: 10.1371/journal.ppat.1006285
|View full text |Cite
|
Sign up to set email alerts
|

Levels of HIV-1 persistence on antiretroviral therapy are not associated with markers of inflammation or activation

Abstract: Antiretroviral therapy (ART) reduces levels of HIV-1 and immune activation but both can persist despite clinically effective ART. The relationships among pre-ART and on-ART levels of HIV-1 and activation are incompletely understood, in part because prior studies have been small or cross-sectional. To address these limitations, we evaluated measures of HIV-1 persistence, inflammation, T cell activation and T cell cycling in a longitudinal cohort of 101 participants who initiated ART and had well-documented sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
136
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(158 citation statements)
references
References 48 publications
19
136
2
1
Order By: Relevance
“…By contrast, in CSFV persistently infected pigs, that showed high and constant viral load, we found a lower CD4/CD8 ratio with respect to naïve or CSFV antibody positive pigs. This finding is in agreement with studies in persistent infection in humans, where the low CD4/CD8 ratio correlated with high viral load and an inability of the immune system to clear the virus (Gandhi et al., ). Also, it has been established that during HIV persistent infection, the T‐cell functions including cytokine secretion and proliferative capacity appear to decrease gradually, being associated with the immune exhaustion phenomenon (Khaitan & Unutmaz, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…By contrast, in CSFV persistently infected pigs, that showed high and constant viral load, we found a lower CD4/CD8 ratio with respect to naïve or CSFV antibody positive pigs. This finding is in agreement with studies in persistent infection in humans, where the low CD4/CD8 ratio correlated with high viral load and an inability of the immune system to clear the virus (Gandhi et al., ). Also, it has been established that during HIV persistent infection, the T‐cell functions including cytokine secretion and proliferative capacity appear to decrease gradually, being associated with the immune exhaustion phenomenon (Khaitan & Unutmaz, ).…”
Section: Discussionsupporting
confidence: 92%
“…Lower CD4/CD8 ratios have been detected in humans suffering persistent and chronic infections with HIV and hepatitis C virus (HCV) (Dustin, 2017). In this regard, a lower CD4/CD8 ratio has also been found in patients with persistently higher HIV-1 viral load (Gandhi et al, 2017).…”
mentioning
confidence: 99%
“…Based on our findings, CMV replication should be considered in future studies dissecting the relationship between HIV reservoir size and immune activation. For example, in a recent longitudinal study of long-term virally suppressed PLWH, correlations between HIV reservoir size and T cell activation were not detected (32). However, immune activation associated with subclinical CMV replication may have confounded the results.…”
Section: Discussionmentioning
confidence: 98%
“…During HIV-1 infection, persistent immune activation and inflammation are driven by multiple factors, including residual virus replication, inflammatory lipids, gut microbial translocation, and coinfection [92][93][94]. Although long-term effective ART substantially reduces the level of immune activation and inflammation in HIV-1-infected individuals, it fails to normalize the activation and inflammation [95][96][97][98][99]. It was reported that persistent T-cell activation was associated with decreased CD4 + T-cell gains in HIV-1-infected individuals during ART 53.…”
mentioning
confidence: 99%